2022
DOI: 10.1186/s40249-021-00927-z
|View full text |Cite
|
Sign up to set email alerts
|

Public and health professional epidemic risk perceptions in countries that are highly vulnerable to epidemics: a systematic review

Abstract: Background Risk communication interventions during epidemics aim to modify risk perceptions to achieve rapid shifts in population health behaviours. Exposure to frequent and often concurrent epidemics may influence how the public and health professionals perceive and respond to epidemic risks. This review aimed to systematically examine the evidence on risk perceptions of epidemic-prone diseases in countries highly vulnerable to epidemics. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Under a major outbreak, the public's perceptions of susceptibility had a small impact on the ultimate level of risk perceptions and probably due to strong control and vaccination policies in China (Kasereka et al, 2019), the public thought they were less likely to be infected. In a study, it was also shown that public risk perceptions are influenced by disease characteristics, particularly disease severity, public familiarity with the disease and manageability (Abdelmagid et al, 2022). Other studies have shown that the perceived likelihood of infection or susceptibility tends to be lower than the perceived severity (Alyousefi et al, 2016; Xu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Under a major outbreak, the public's perceptions of susceptibility had a small impact on the ultimate level of risk perceptions and probably due to strong control and vaccination policies in China (Kasereka et al, 2019), the public thought they were less likely to be infected. In a study, it was also shown that public risk perceptions are influenced by disease characteristics, particularly disease severity, public familiarity with the disease and manageability (Abdelmagid et al, 2022). Other studies have shown that the perceived likelihood of infection or susceptibility tends to be lower than the perceived severity (Alyousefi et al, 2016; Xu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Public attitude can be crucial in the attempt to fight infectious diseases. Public knowledge and understanding of basic needs and scientific progresses regarding specific infections are important prerequisites, since acceptance of scientific advances and agreement to comply with voluntary measures, such as vaccination and isolation, can increase protection of public health measures leading to control of the disease [ 23 ]. To that direction, understanding the existing misconceptions and educational gaps can be of utmost importance leading to organization of interventions that can increase awareness and compliance to suggested practices [ 24 ].…”
Section: Discussionmentioning
confidence: 99%